Pengaruh Motivasi dan Lingkungan Kerja terhadap Disiplin Kerja Karyawan Pada PT. Asuransi Tri Pakarta di Denpasar - Farae Tody, Dewa Ketut Agung; Hartati, Putu Sri; Sugianingrat, Ida Ayu Putu Widani (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The implementation of work discipline is the initial capital in the smooth completion of tasks in a company. The purpose of this study was to determine the effect of work motivation and work environment on work discipline on employees of PT Asuransi Tri Pakarta Denpasar.  The number of samples was determined as many as 35 respondents using the saturated sample method. The research method used in this study and instrument test, classical assumption test, multiple linear regression, coefficient of determination, t test and F test. The results showed that: (1) work motivation had a positive and significant effect on employee work discipline (2) the work environment had a positive and significant effect on work discipline. Work Motivation and Work Environment simultaneously have a significant effect on Work Discipline at PT Asuransi Tri Pakarta Denpasar. Suggestions that can be given to PT. It is hoped that the Tri Pakarta Denpasar Insurance company leadership can readjust the income or salary received by its employees according to the workload and which can reduce work discipline and it is hoped that the company leadership will try to provide a room that is protected from noise from the surrounding environment.